Analisis Strategi Keunggulan Bersaing UMKM Circle Store Di Kabupaten Bone: Pendekatan Swot Sebagai Kunci Sukses Bisnis Lokal - Sitti Hasbiah (Trending: Jurnal Manajemen dan Ekonomi, 2024)
In the dynamic business era, UMKM Circle Store has come under scrutiny, facing various strengths and challenges. This phenomenon serves as the focal point of research to gain a profound understanding of the internal strengths, external opportunities, weaknesses, and threats that Circle Store may encounter. The research aims to identify key factors influencing the business performance of UMKM Circle Store, particularly through the SWOT approach. A qualitative research method was employed, involving in-depth interviews, direct observations, and analysis of relevant documents. This identification process is carried out through internal and external factors, IFAS and EFAS, as well as the SWOT matrix. The research findings reveal that the internal factor or IFAS attains an overall score of 3.51, while the external factor or EFAS obtains an overall score of 3.82. This indicates the potential to optimize strengths and opportunities while minimizing weaknesses and threats.